Feeding behaviour of goats in the southern rangelands of Ethiopia - Dessalegne, B. (International Livestock Centre for Africa, 1985)
A study on the feeding behaviour of forty adult female goats at Beke in the southern rangelands of Ethiopia carried to determine the type of vegetation consumed and the amount of time spent on different activities like walking, feeding, ruminating & idling.